Pregnancy Outcomes After Different Cycle Regimens for Frozen-Thawed Embryo Transfer: A Retrospective Study Using Propensity Score Matching - Wang, Bian; Zhu, Qianqian; Wang, Yun (Frontiers in Medicine, 2020)
Background: Nowadays, the choice of the frozen embryo transfer (FET) regimens is mainly guided by personal convenience. The clinicians prefer the predictability and reliability of artificial cycle (AC-FET) and have extended its usage to general IVF population. More recent primary studies are beginning to challenge the comparability of AC-FET and suggest a reduced CPR and LBR compared with modified natural cycle (mNC-FET, ovulation triggered by HCG) and stimulated cycle (SC-FET). Objective: To assess the pregnancy outcomes within matched mNC-FET, SC-FET and AC-FET cycles by using propensity score matching (PSM) in a larger cohort. Methods: A total of 16946 women who underwent their first autologous FET cycle between July 2014 and July 2017 were evaluated. PSM using the nearest neighbor matching，were established to adjust the baseline features within the three protocols in proportion of 1:1 (mNC-FET vs SC-FET, mNC-FET vs AC-FET, SC-FET vs AC-FET, respectively). And there were 3567, 2917 and 3964 cycles compared between matched mNC-FET and SC-FET, mNC-FET and AC-FET, SC-FET and AC-FET after the PSM, respectively. Results: LBR was significant lower in the AC-FET group than in the mNC-FET (40.0% vs 43.3%) and SC-FET groups (40.9% vs 46.5%). The adjusted ORs (95%CIs) were 1.11(1.00, 1.24) for mNC/AC (P=0.044) and 0.84(0.76, 0.92) for AC/SC (P<0.001), which indicated that the AC-FET group was associated with lowest LBR. The LBR was comparable between matched mNC-FET and SC-FET after adjusting for endometrial thickness (EMT). Moreover, a lower CPR and a higher risk of early pregnancy loss were discovered in AC-FET cycles compared to SC-FET. Conclusion: In view of our data, artificial cycle used for scheduling FET was associated with lower LBR compared with stimulated cycle and modified natural cycle. This interpretation requires future verification from well-designed prospective multicenter randomised clinical trials (RCTs) even though the comparisons in our study were conducted in the homogenous population after the PSM.